PERANCANGAN SISTEM INFORMASI AKADEMIK PASRAMAN BERBASIS WEBSITE - Prasetyo, Yudho; Prasetyo, Koko Wahyu; Kanthi, Yekti Asmoro (DINAMIKA DOTCOM, 2019)
Pasraman is a Hindu education institution to assist the implementation of religious education and manners that highlight the growing attitude and skills as a strengthening of the local culture. Pasraman is a religious educational institution, where the existence of Pasraman are expected to embody one of the goals of the Republic of Indonesia. Pasraman Upanisadha is one of the formal pasraman located in Kupang, East Nusa Tenggara, which consists of a hierarchy of Pratama Widya Pasraman, Adi Widya Pasraman, Madyama Pasraman, Utama Widya Pasraman, and Maha Widya Pasraman. The existence of this judgment on the pasraman system Upanisadha can be accessed directly by parents, and the school of brahmacari get access rights to see the hindu value of their students. On the features of financial SPP and the dana punia, accessible by Chairman of the Pasraman, brahmacari, parents of brahmacari, and administration is transparent so reducing the possibility of fraud. By having this system, pasraman will be balanced and able to compete with other formal school.Keywords: System, Information, Academic, Pasraman, Website